2023
DOI: 10.3791/65299
|View full text |Cite
|
Sign up to set email alerts
|

Fu's Subcutaneous Needling for Knee Osteoarthritis Pain

Abstract: Fu's subcutaneous needling (FSN) is a new acupuncture and dry needling technique based on traditional Chinese medicine. It rapidly produces long-lasting effects in soft tissue injuries, particularly in painful musculoskeletal conditions, by providing stimulation primarily in the subcutaneous area. Osteoarthritis (OA) is the most common joint disease in adults worldwide and is often accompanied by a painful syndrome of structural changes in the peripheral joints of the knee. However, the etiology of OA pain is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This technique is highly targeted and can correct misaligned cervical vertebral joints and hooked vertebral joints, which is beneficial for tissue edema and inflammation around nerve roots to subside, thereby quickly alleviating clinical symptoms. Fu's Subcutaneous Needling is an application form of suitable techniques in traditional Chinese medicine, and it is a new type of acupuncture therapy evolved from traditional acupuncture and moxibustion therapy combined with modern diagnosis and treatment technology [14] [15][16] . Fu's Subcutaneous Needling often use the scanning and dispersing technique, which is based on the special structure of skin connective tissue, that is, the mechanism of sensitivity to piezoelectric effect by utilizing the spatial arrangement of matrix spiral molecules in connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is highly targeted and can correct misaligned cervical vertebral joints and hooked vertebral joints, which is beneficial for tissue edema and inflammation around nerve roots to subside, thereby quickly alleviating clinical symptoms. Fu's Subcutaneous Needling is an application form of suitable techniques in traditional Chinese medicine, and it is a new type of acupuncture therapy evolved from traditional acupuncture and moxibustion therapy combined with modern diagnosis and treatment technology [14] [15][16] . Fu's Subcutaneous Needling often use the scanning and dispersing technique, which is based on the special structure of skin connective tissue, that is, the mechanism of sensitivity to piezoelectric effect by utilizing the spatial arrangement of matrix spiral molecules in connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The patient in the present case study was subjected to FSN therapy, a method that combines traditional Chinese acupuncture and dry needling. Studies have reported that FSN is efficacious against various soft tissue injuries and medical issues, [ 7 9 , 11 , 12 ] recent studies [ 13 , 14 ] reveal that stretching subcutaneously can influence adjacent VA and FSN may enhance gastrointestinal motility and decrease gastric drainage volume. Unlike traditional Chinese acupuncture methods that may involve deep needle insertion, FSN entails the shallow insertion of a disposable needle into the subcutaneous area near the affected muscle, referred to as the “tightened muscle” with one or more MTrPs.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the patient condition and facilitate early weaning from the ventilator, we employed FSN therapy. [ 8 , 11 ] Results from touch-based physical examination revealed the presence of myofascial trigger points (MTrPs) around his neck, chest, and abdomen (Fig. 1 A and B).…”
Section: Case Presentationmentioning
confidence: 99%
“…Operation of the FSN follows the KOA's Fu's Subcutaneous Needling Treatment Code of Practice 24 . Participants rst assume the supine position.…”
Section: Fsn Therapymentioning
confidence: 99%